Study choice preferences of seconardy school students: Who decides to pursue a STEM degree and for what reasons? - Aeschlimann, Belinda; Herzog, Walter; Makarova, Elena (Swiss Journal of Educational Research, 2018)
The article analyzes the study choice preferences of Swiss-German secondary school students. The central question focuses on the reasons why prospective students (de-)select a course of study in science, technology, engineering, and mathematics (STEM). We take into consideration both individual and contextual factors. The results show that the gender of the young people, as well as their interest and their achievement in mathematics and natural science subjects have the greatest predictive power for a STEM study choice. Moreover, the intrinsic study choice motives of high school students act as essential determinants of the selection or de-selection of a STEM degree.